Abecedna razvrstitev knjižničnega gradiva v oddelku programa z nižjim izobrazbenim standardom - Markič, Nataša (Šolska knjižnica, 2014)
The paper presents a comparison of one lesson of Library and information knowledge (KIZ) in a regular primary school class with a lesson in a class with lower-level educational standard. It demonstrates the differences in the class work (number of students, their age and specific learning difficulties).KIZ lessons in the class with lower-level educational standard are adapted to the group and to the specific difficulties of the special needs students. Much more time and practice is needed. It is especially important that these students maintain their love of books and library space.
Keywords: knjižnično informacijsko znanje; opismenjevanje; osnovne šole; šolske knjižnice; učenci s posebnimi potrebami